Eleventh Dynasty Written Evidence on the Relationship between the k˒͗ and the Cult Image - Demidchik, Arkadiy E. (Zeitschrift für ägyptische Sprache und Altertumskunde, 2015)
The article points to some additional written evidence on the relation between the k˒͗ -concept and the cult image. It is argued that connection with the latter was essential and inherent for the ḥw.t-k˒͗ and the service of the ḥm-k˒͗ . The inscriptions on JE 46068, BM EA 627 and BM EA 1164, by highlighting the cult image- twt as recipient of the boons provided for the k˒͗ , almost equate these two notions, that is best explainable if the cult image was considered as “door” for the k˒͗ ’s “going forth”. Such revealing deviations from the Old Kingdom written tomb etiquette may have been induced by the rarity of tomb sculpture and some innovations in its use in the First Intermediate Period.